2022
DOI: 10.1002/pon.6047
|View full text |Cite
|
Sign up to set email alerts
|

Developing theory‐driven narrative messages with personal stories: A step‐by‐step guide

Abstract: Objective: Narratives are commonly utilized in health promotion and behavior change interventions due to their efficacy over didactic or expository interventions.While grounding narratives in behavioral theory may render them more effective, balancing the integration of theoretical and creative aspects of the narrative development process while maintaining authenticity is challenging. Thus, this manuscript describes a rigorous process through which researchers can intentionally integrate theory and personal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
(96 reference statements)
0
0
0
Order By: Relevance
“…Third, as alluded to above, we included patients’ experiences with sharing VUS results, as well as sharing their family history of cancer. Integrating patient narratives such as quotes provides psychosocial information that resonates with patients, helping them to process and manage information [ 44 ] and may motivate them to adopt certain health behaviors [ 45 ]. Specific quotes that illustrate different coping responses can demonstrate appropriate cancer risk management decisions and forecast possible reactions that family members may have if patients share information [ 46 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Third, as alluded to above, we included patients’ experiences with sharing VUS results, as well as sharing their family history of cancer. Integrating patient narratives such as quotes provides psychosocial information that resonates with patients, helping them to process and manage information [ 44 ] and may motivate them to adopt certain health behaviors [ 45 ]. Specific quotes that illustrate different coping responses can demonstrate appropriate cancer risk management decisions and forecast possible reactions that family members may have if patients share information [ 46 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specific quotes that illustrate different coping responses can demonstrate appropriate cancer risk management decisions and forecast possible reactions that family members may have if patients share information [ 46 , 49 ]. A novel aspect of this section in our intervention is the use of real patients’ quotes from extant research [ 44 ], as well as interviews from our prior study. Importantly, our participants who evaluated the educational materials reported that the patients’ quotes resonated with their personal experiences when sharing their VUS result and/or family history of cancer with family members.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations